HbA1c, Coronary atheroma progression and cardiovascular outcomes - Iryna Dykun; Ozgur Bayturan; Julie Carlo; Steven E. Nissen; Samir R. Kapadia; E. Murat Tuzcu; Stephen J. Nicholls; Rishi Puri (Elsevier, 2022)
Background and aims: We tested the hypothesis that on-treatment HbA1c levels independently associate with coronary atheroma progression and major adverse cardiovascular events (MACE: death, myocardial infarction, cerebrovascular accident, coronary revascularization, or hospitalization for unstable angina) rates. Methods: We performed a post-hoc pooled analysis of data from seven prospective, randomized trials involving serial coronary intravascular ultrasonography (IVUS). The percent atheroma volume (PAV) was calculated as the proportion of the entire vessel wall occupied by atherosclerotic plaque. Using multivariable mixed modeling, we determined the association of on-treatment HbA1c with annualized change in PAV. Cox proportional hazard models were used to assess the association of HbA1c with incidence of MACE. Results: Among 3,312 patients (mean age 58.6±9years, 28.4%women) average on-treatment HbA1c was 6.2±1.1%. Overall, there was no net significant annualized change in PAV (0.12±0.19%, p = 0.52). In a fully adjusted multivariable analysis (following adjustment of age, sex, body mass index, systolic blood pressure, smoking, low- and high-density lipoprotein cholesterol, triglyceride levels, peripheral vascular disease, trial, region, and baseline PAV), higher on-treatment HbA1c levels were independently associated with annualized changes in PAV [beta-estimate (95% confidence interval): 0.13(0.08, 0.19), p < 0.001]. On-treatment HbA1c levels were independently associated with MACE [hazard ratio (95% confidence interval): 1.13(1.04, 1.23), p = 0.005]. Conclusions: Independent of achieved cardiovascular risk factor control, greater HbA1c levels significantly associate with coronary atheroma progression rates and clinical outcomes. These results support the notion of a direct, specific effect of glycemic control upon coronary atheroma and atherosclerotic events, supporting the rationale of therapies designed to directly modulate it.